Evaluation of the Updated Diagnostic Criteria for Paraneoplastic Neurologic Syndromes in China - Cai, Meng-Ting; Qiao, Song; Lai, Qi-Lun; Zheng, Yang; Yang, Fan; Fang, Gao-Li; Shen, Chun-Hong; Zhang, Yin-Xi; Ding, Mei-Ping (Frontiers in Immunology, 2022)
Background: Recently the paraneoplastic neurologic syndromes (PNSs) diagnostic criteria have received a major update with a new score system over the past 16 years. We aimed to evaluate the diagnostic performance and clinical utility in China. Methods: An eligible cohort of 113 Chinese patients diagnosed as PNSs from Second Affiliated Hospital School of Medicine Zhejiang University and published data were enrolled retrospectively. Data including clinical phenotype, antibody type, the presence of cancer, and duration of follow-up were reviewed and re-evaluated to classify the diagnostic levels for the 2004 and 2021 PNS criteria. The performances of these 2 criteria were compared. The critical parameters of antibody and cancer for the updated criteria were further explored. Results: The cohort consisted of 69 males and 44 females with a median age of 60 years. Limbic encephalitis (23, 20.4%), anti-Hu antibody (32, 28.3%), and small-cell lung cancer (SCLC) (32, 28.3%) were the most common clinical phenotype, detected antibody and concomitant cancer respectively. A total of 97 (85.8%) patients were diagnosed as definite PNS according to the 2004 criteria, whereas only 42.3% (41/97) fulfilled the 2021 criteria, while the remaining 40, 14 and 2 were re-diagnosed as probable, possible and non-PNS. The requirement of cancers consistent with antibody and phenotype increased the specificity and thus greatly enhanced the accuracy of the 2021 criteria. Conclusion: The updated criteria for PNS emphasized the consistency between cancer phenotype and antibody, and showed a better diagnostic value. The better diagnostic yield could benefit disease management.